Yes, Chef! : it's snack time - Love, Charlotte (New York : Grosset & Dunlap, an imprint of Penguin Random House LLC, 2024)
"A delightful call-and-response board book that introduces kids to simple cooking skills from creator Charlotte Love"--.
Ages 1-3.
Keywords: Fruit -- Fiction; Board books; Cooking -- Fiction; Board books; Picture books